Do general intellectual functioning and socioeconomic status account for performance on the Children's Gambling Task? - Mata, Fernanda; Miranda, Debora M.; Sallum, Isabela; Bechara, Antoine; Malloy-Diniz, Leandro F. (Frontiers in Neuroscience, 2013)
Studies that use the Iowa Gambling Task and its age-appropriate versions as indices of affective decision-making during childhood and adolescence have demonstrated significant individual differences in scores. Our study investigates the association between general intellectual functioning and socioeconomic status and its effect on the development of affective decision-making in preschoolers by using a computerised version of the Children’s Gambling Task (CGT). We administered the CGT and the Columbia Mental Maturity Scale (CMMS) to 137 Brazilian children between the ages of 3 and 5 years old to assess their general intellectual functioning. We also used the Brazilian Criterion of Economic Classification (CCEB) to assess their socioeconomic status. Age differences between 3-and 4-year-olds, but not between 4-and 5-year-olds, confirmed the results obtained by Kerr and Zelazo (2004), indicating the rapid development of affective decision-making during the preschool period. Both 4- and 5-year-olds performed significantly above chance on blocks 3, 4 and 5 of the CGT, whereas 3-year-olds’ mean scores did not differ from chance. We found that general reasoning ability was not related to affective decision-making. On the other hand, our findings showed that children with high socioeconomic status (SES) performed better on the last block of the CGT in comparison to children with low SES. We also found that more children from the high SES group performed better in comparison to children from the low SES group, which indicates that children from the former group seem more likely to use the information about the gain/loss aspects of the decks to efficiently choose cards from the advantageous deck throughout the task.